New York, Monterrey and Paris: three contradictory logics facing the challenges of development in the first decade of the century - UNCETA SATRÚSTEGUI, Koldo; MARTÍNEZ HERRERO, María José; ZABALA ERRAZTI, Idoye (Revista Iberoamericana de Estudios de Desarrollo)
This paper analyzes the contradictory logics raised along the first decade of xxi century from major international forums which have debated about Development Cooperation. For this purpose, we have studied the different approaches proposed since the adoption of the Millennium Declaration until the recent High Level Forum in Busan, differentiating among the questions related to the Goals, those relating to Finance, and these that have to do with the management and Aid Effectiveness. The paper concludes that these logics have lacked a shared diagnosis of some of the major problems. This has promoted inconsistent practices and a scarcely coherent approach, which makes it difficult a consistent progress in this field.